Current Capacities of Forensic Psychological and Comprehensive Analysis When Examining Footage of Procedural and Non-Procedural Actions - T. N. Sekerazh (Теория и практика судебной экспертизы)
The article addresses some typical situations arising in the course of a forensic psychological examination of footage when it is necessary to establish the following factual data: signs of the credibility of the information reported, spontaneity and preparedness of an interrogated person’s speech, external influence on the given testimony, the emotional state of the interrogated person and his/her psychological characteristics. The author analyses the situations that arise when examining the footage showing informal communication. The article also determines the range of tasks to solve which, the expert needs various specialized knowledge, primarily in the fields of forensic psychology and linguistics. Expert tasks occurring in forensic analysis of the footage of procedural and non-procedural actions depend on the case’s category, significance and procedural status of the footage in the evidentiary framework on the case, and some other factors. The author pays particular attention to the scope of expert competence for different specialties, including on the issues that cannot be solved by expert means at the current stage of scientific development.